Cross-Border Price Effects of Mergers and Acquisitions – A Quantitative Framework for Competition Policy - Holger Breinlich; Volker Nocke; Nicolas Schutz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Decisions of national competition authorities have important effects on other jurisdictions. We provide a framework to quantify the domestic and cross-border effects of mergers, and to draw conclusions for the coordination of national merger policies. We develop a two-country model with many sectors. In each sector, producers vary in terms of their marginal costs, and are engaged in Cournot competition. We allow for profitable mergers to take place subject to the non-violation of a given national competition policy. Because of trade costs and perceived differences in qualities between domestic and foreign products, mergers may have different consumer surplus effects in the home and the foreign country. We calibrate the model using data for the year 2002 for 167 manufacturing sectors in the U.S. and Canada. We choose parameters to match relevant moments in the data, including industry sales, concentration ratios and trade flows. We find that in the majority of industries a merger approval policy based on domestic consumer surplus is too restrictive from the viewpoint of the neighboring country. We also show that adopting a supra-national policy that approves a merger if and only if it increases the sum of consumer surplus in the two countries would lead to significant gains for U.S. consumers but hurt consumers in Canada. These results highlight the difficulties in coordinating national competition policies in a way acceptable to all participating countries.
Keywords: F12; L44; L13; 330